Evaluating the efficacy of medium chain fatty acids (MCFA) as a replacement for zinc oxide (ZnO) and carbadox in nursery pig diets - Comstock, Cara J.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
Increased pressure on the agriculture to limit antibiotics in livestock has forced the industry to look for alternative diets. This trial assessed if Medium Chain Fatty Acids (MCFA) can replace Zinc Oxide(ZnO) or carbadox in nursery pig diets. In this experiment, diets of varying levels of MCFA were fed to 360 nursery pigs (DNA 200x400);5.4±kg) in a completely randomized design with 6 pigs/pen and 10 replicates. Replicates were fed one of six treatments: 1) control 2) 3,000 ppm ZnO (phase 1), 1500 ppm ZnO (phase 2); 3) 50g/ton carbadox; 4) 1% blend C6:C8:C10; 5) 1% Feed Energy R2(Feed Energy Corp., Des Moines, IA); 6) 1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany). The treatment period was split into two dietary phases: Phase 1: d0 to 7; Phase 2: d8 to 19, with a common phase 3, d20 to 35. Data was analyzed using the GLIMMIX procedure of SAS (SAS Inst., Cary, NC.). Pigs fed the ZnO diet were significantly different from those fed control, C6C8C10 and R2 diets. Pigs fed ZnO had similar results to those fed carbadox and FORMI. (P<0.0001). Pigs fed C6C8C10 and R2 diets had significantly different results from those on the ZnO diet, while C6C8C10, R2 and FORMI were all similar to carbadox (P=0.012). ZnO outperformed the control, C6C8C10 and R2 diets. Feed intake of pigs fed Treatments C6:C8:C10 and FORMI were not significantly different from ZnO (P=0.012) for ADG for days 0 to 35. These results suggest that there were no significant differences in using the R2 or FORMI diets to replace Zinc Oxide or Carbadox for use in promoting growth in nursery pigs. Further research needs to be conducted on MCFA in nursery pigs.
Keywords: Spring 2019